2018
DOI: 10.3390/su10072574
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Influences of Economic Development, Energy Consumption, Urbanization, Industrialization, and Vehicles Amount on PM2.5 Concentrations of China

Abstract: The speeding-up of economic development and industrialization processes in China have brought about serious atmospheric pollution issues, especially in terms of particulate matter harmful to health. However, impact mechanisms of socio-economic forces on PM2.5 (the particle matter with diameter less than 2.5 μm) have rarely been further investigated. This paper selected GDP (gross domestic product) per capita, energy consumption, urbanization process, industrialization structure, and the amount of possession of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 46 publications
2
20
1
Order By: Relevance
“…The impulse response function indicated that economic growth of the primary and secondary industries can raise PM 2.5 emissions, whilst the tertiary industry had an inhibitory effect. This result is consistent with the findings of Cao [67] and Zhao [68]. Therefore, it can be found that industry improvement (defined as economic growth) is an important factor affecting the intensity and direction of PM 2.5 emissions.…”
Section: Discussionsupporting
confidence: 92%
“…The impulse response function indicated that economic growth of the primary and secondary industries can raise PM 2.5 emissions, whilst the tertiary industry had an inhibitory effect. This result is consistent with the findings of Cao [67] and Zhao [68]. Therefore, it can be found that industry improvement (defined as economic growth) is an important factor affecting the intensity and direction of PM 2.5 emissions.…”
Section: Discussionsupporting
confidence: 92%
“…It suggests that the demand for energy consumption in China is still huge. To effectively control the rapid growth of energy consumption, the current economic development pattern and urbanization mode that rely heavily on natural resources and ecological environment [49][50][51][52] should be adjusted. For instance, China should promote the development of a low-carbon economy by accelerating the development of tertiary industry and industries with new technology and high added-values.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Some studies have briefly discussed the impact of different types of urbanization (e.g., population, economic and land urbanization) on air quality and the atmospheric environment [14,15]. With reforms in the household registration system and the rise of small cities, China's population urbanization (PU) level has rapidly increased, resulting in the widespread use of kitchen fumes and cars and generating large amounts of PM 2.5 pollutants in daily life [16,17].…”
Section: Introductionmentioning
confidence: 99%